Social competence in newly diagnosed pediatric brain tumor patients. (2nd January 2020) - Kok, Tessa B.; Koerts, Janneke; Lemiere, Jurgen; Post, Wendy J.; de Bont, Eveline S. J. M.; Gidding, Corrie; Happé, Franscesca; Jacobs, Sandra; Oostrom, Kim; Schieving, Jolanda; Tucha, Oliver; Kingma, Annette
Abstract: Brain tumors (BTs) are a common pediatric malignancy. Improved treatment has resulted in higher survival rates. There is, however, increasing concern about adverse effects of the disease and its treatment, including effects on social competence (i.e. effective social functioning in everyday life). The aim of this study is to examine multiple levels of social competence (i.e. social skills and social adjustment) in newly diagnosed pediatric BT patients. Thirty newly diagnosed BT patients aged 5–12 years were assessed shortly after diagnosis with a neuropsychological test battery focusing on social competence, including tests for IQ, social skills (i.e. social-affective and executive functioning) and social adjustment (rated by parents and teachers). Their performance was compared to 95 healthy controls who completed the same assessment. Patients and healthy controls were largely comparable with regard to demographic and environmental factors and did not differ on measures of IQ, social skills and social adjustment. Furthermore, age was found to have a positive significant effect on social skills independent of group. Shortly after diagnosis, pediatric BT patients did not perform different from healthy controls on IQ and measures of social skills and social adjustment. This is an encouraging finding. However, because of potentially neurotoxic adjuvant therapy and the ongoing development of social skills, longitudinal follow-up studies are needed to investigate long-term outcome regarding social competence in BT survivors.